Hubungan Komunikasi Interpersonal Guru Bimbingan dan Konseling dengan Self Efficacy Peserta Didik - Ujung, Nursholihat; Arsini, Yenti (Fakultas Tarbiyah dan Keguruan, 2024)
This study aims to analyze the relationship between the interpersonal communication of guidance and counseling teachers and the self-efficacy of students at MTs N 2 Medan. The research employs a quantitative approach with a correlation design. The sample consists of 192 students selected using simple random sampling. The instruments used in this study include the interpersonal communication scale and the self-efficacy scale. Data were collected and analyzed using SPSS version 23 for Windows, with Pearson correlation analysis used to measure the relationship between variables. The results indicate that the interpersonal communication of guidance and counseling teachers is categorized as moderate, with an average percentage of 74.6%, while students' self-efficacy is also categorized as moderate, with an average percentage of 72.84%. Data analysis reveals a positive and significant relationship between the interpersonal communication of guidance and counseling teachers and self-efficacy, with an r value of 0.710 and Sig. 0.000 (p < 0.05). This indicates a strong correlation between interpersonal communication and self-efficacy. Higher quality interpersonal communication by guidance and counseling teachers is associated with higher levels of student self-efficacy, and conversely, lower quality communication is associated with lower self-efficacy. The conclusion of this study is that effective interpersonal communication contributes to increased student self-efficacy. The practical implication of these findings emphasizes the importance of improving the quality of communication between guidance and counseling teachers and students to support the development of their self-efficacy.